Effects of bubble cutting dynamic behaviors on microalgal growth in bubble column photobioreactor with a novel aeration device - Zhao, Sha; Feng, Wenyue; Li, Jinming; Zhang, Xiaoguang; Liu, Li; Li, Hongyan (Frontiers in Bioengineering and Biotechnology, 2023)
Carbon sequestration by microalgae is an effective approach for achieving carbon neutrality owing to its high carbon capture efficiency and environmental friendliness. To improve microalgae CO2 fixation efficiency, various methods to enhance CO2 transfer at the gas-liquid interface have resulted in high energy consumption. Methods: In this study, a novel aeration device with bubble cutting slices was installed in a photobioreactor for CO2 supply, which could precisely separate bubbles into sizes on the way to rising after departure, achieving CO2 transfer enhancement without extra energy consumption. Subsequently, the bubble cutting dynamic behaviors in the photobioreactor were studied, and the effects of thickness, hydrophilicity, and arrangement of cutting slices on microalgal growth were analyzed. Results: It was found that bubble cutting caused the maximum dry weight and biomass productivity of microalgae to improve by 6.99% and 33.33%, respectively, compared with those of the bioreactor without cutting units, owing to a 27.97% and 46.88% decrease in bubble size and rising velocity, respectively, and an 84.55% prolongation of bubble residence time. Discussion: Parallel cut slices with a thickness and spacing of less than 3 mm successfully cut the bubbles. The hydrophobic slice surface prevented daughter bubble departure and prolonged the bubble residence time, impeding microalgae growth owing to bubble coalescence with subsequent bubbles. The optimal cutting slice parameters and culture conditions for microalgal growth were 1 mm slice thickness, less than 1 mm slice spacing, 5% inlet CO2 concentration, and 70 mL/min gas flow rate.